Value Added Tax Analysis of Freight Forwarding Services at PT B Denpasar - P Candrastuti Putri; N S Hardika; C Ardina (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
Freight forwarding services or transportation management services aim to represent the task of shipping goods (consignor/ shipper/ exporter) to destination either by land, sea, or air. Freight forwarding services does not only consist of one service, but there are many services related to shipping and receiving goods to form freight forwarding service. In delivering goods, freight forwarders usually work with partners to carry out and provide services. The value added tax (VAT) law and its regulations have not specifically regulated the treatment of value added tax on freight forwarding services, especially in the payment method. The Reinvoicing method is a method by which freight forwarder create new invoices to collect service fees from freight forwarding plus fee from work partner. Reimbursement method where freight forwarder forward work partner invoice so that PT B receives two invoice in which there was a value added tax in (VAT In) that cannot be credited. The result of the study suggests that PT B in collaboration with PT I as a freight forwarder chooses a reinvoicing method because it is more efficient and shows a better impact on the cash flow statement.